Literature review: Maturity Onset Diabetes of the Young (MODY) - Bramantyo, Rofi; Fauzan, Naufal Revaldy; Wahyudi, Reza Rizwandipa; Dzulilmi, Dhaifatu; Putri, Septy Rianty Salsabilla Dwi; Prameswari, Devi Shanti; Dhevi, Ni Made Shaithanya Gitanjali; Putri, Alifia Sabira; Maudina, Baiq Zaskia; Rizqi, Amanda Suana; Salsabila, Ruhaniah Najwa; Wardani, Indah Sapta (Jurnal Biologi Tropis, 2025)
Maturity Onset Diabetes of the Young (MODY) is a group of monogenic genetic disorders that cause diabetes with an autosomal dominant inheritance pattern, generally appearing before the age of 25. MODY is caused by gene mutations affecting pancreatic beta cell function, with 14 genetic subtypes identified. Diagnosis is often delayed or incorrect, as symptoms resemble type 1 or type 2 diabetes. The diagnosis of MODY is diagnosed through family history, clinical examination, and genetic analysis. MODY treatment is tailored to the genetic subtype, including lifestyle changes, sulfonylureas, and insulin, is tailored to the genetic subtype. Prognosis and risk of complications vary depending on the subtype, with MODY 2 (GCK) having the best prognosis. Prevention includes genetic testing for individuals with a family history of MODY, as well as lifestyle modifications to reduce the risk of complications. Patient education is important to ensure optimal management and prevention of long-term complications. This journal aims to learn more about the following definitions, to prognosis and education of MODY.